The effect of regional white matter hyperintensities on essential tremor subtypes and severity - He, Runcheng; Qin, Yan; Zhou, Xun; Liu, Zhenhua; Xu, Qian; Guo, Jifeng; Yan, Xinxiang; Tang, Beisha; Zeng, Sheng; Sun, Qiying (Frontiers in Aging Neuroscience, 2022)
Objectives To investigate the effect of regional white matter hyperintensities (WMHs) on Essential tremor (ET) subtypes and to explore the association between WMHs load and the severity of motor and non-motor symptoms in patients with ET. Methods A cohort of 176 patients with ET (including 86 patients with pure ET and 90 patients with ET plus) and 91 normal controls (NC) was consecutively recruited. Demographic, clinical, and imaging characteristics were compared between individuals with pure ET, ET plus, and NC. The cross-sectional association among regional WMHs and the severity of tremor and non-motor symptoms were assessed within each group. Results Compared with the pure ET subgroup, the ET plus subgroup demonstrated higher TETRAS scores, NMSS scores, and lower MMSE scores (all P < 0.05). Periventricular and lobar WMHs' loads of pure ET subgroup intermediated between NC subjects and ET plus subgroup. WMHs in the frontal horn independently increased the odds of ET (OR = 1.784, P < 0.001). The age (P = 0.021), WMHs in the frontal lobe (P = 0.014), and WMHs in the occipital lobe (P = 0.020) showed a significant impact on TETRAS part II scores in the ET plus subgroup. However, only the disease duration was positively associated with TETRAS part II scores in patients with pure ET (P = 0.028). In terms of non-motor symptoms, NMSS scores of total patients with ET were associated with disease duration (P = 0.029), TETRAS part I scores (P = 0.017), and WMH scores in the frontal lobe (P = 0.033). MMSE scores were associated with age (P = 0.027), body mass index (P = 0.006), education level (P < 0.001), and WMHs in the body of the lateral ventricle (P = 0.005). Conclusion Our results indicated that the WMHs in the frontal horn could lead to an increased risk of developing ET. WMHs may be used to differentiate pure ET and ET plus. Furthermore, WMHs in the frontal and occipital lobes are strong predictors of worse tremor severity in the ET plus subgroup. Regional WMHs are associated with cognitive impairment in patients with ET.